2015
DOI: 10.1007/s11740-015-0615-x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the cutting edge radius on surface integrity in hard turning of roller bearing inner rings

Abstract: Hard turning is used as a finishing process to machine hardened parts with very high accuracies. During the last decades it asserted as an alternative to conventional grinding processes due to higher flexibility and productivity. Furthermore, hard turning also increases positive effects on the surface integrity compared to grinding processes. Process parameters such as cutting speed, feed and cutting edge geometry influence the effect on subsurface area as well as the surface roughness. Many researchers have b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 17 publications
1
14
0
Order By: Relevance
“…The residual stresses were measured with an X-ray diffractometer Seiffert XRD 3000 P using CrKa radiation. The experimental procedure and results are described in detail by Denkena et al [13,14].…”
Section: Machining Of Roller Bearings With Specific Residual Stress Dmentioning
confidence: 99%
“…The residual stresses were measured with an X-ray diffractometer Seiffert XRD 3000 P using CrKa radiation. The experimental procedure and results are described in detail by Denkena et al [13,14].…”
Section: Machining Of Roller Bearings With Specific Residual Stress Dmentioning
confidence: 99%
“…6 Varela et al 22 observed that cutting edges with combined chamfer and hone produce higher compressive residual stress at the workpiece surface in comparison to single honed tools, what was attributed to the significant plowing effect. Investigating the effect of different edge roundings on residual stress, Denkena et al 23 noted that an increase in edge radius causes an increase in maximum compressive residual stress and an increase in the affected subsurface zone. The authors affirm that this effect can be related to the increase in passive force, which causes high mechanical loads on the workpiece surface.…”
Section: Introductionmentioning
confidence: 99%
“…The results revealed that the tiny grooves, severe plastic flow, and extensive material flows at lower feeds have significant influence on the surface integrity. Denkena et al [12] studied the effect of cut ting speed, feed and cutting edge radius on the surface integrity in terms of the surface roughness, residual stress, and microstructure and hardness by summarizing overview to identify the optimal parameter value and improve the endurance of roller bearings. Domenico et al [13] explored the effects of different cooling con ditions on white layer.…”
Section: Introductionmentioning
confidence: 99%